Derivation of pancreatic acinar cell carcinoma cell line HS‐1 as a patient‐derived tumor organoid. Issue 3 (27th November 2022) - Hoshi, Daisuke; Kita, Emiri; Maru, Yoshiaki; Kogashi, Hiroyuki; Nakamura, Yuki; Tatsumi, Yasutoshi; Shimozato, Osamu; Nakamura, Kazuyoshi; Sudo, Kentaro; Tsujimoto, Akiko; Yokoyama, Ryo; Kato, Atsushi; et al.
Abstract: Acinar cell carcinoma (ACC) of the pancreas is a malignant tumor of the exocrine cell lineage with a poor prognosis. Due to its rare incidence and technical difficulties, few authentic human cell lines are currently available, hampering detailed investigations of ACC. Therefore, we applied the organoid culture technique to various types of specimens, such as bile, biopsy, and resected tumor, obtained from a single ACC patient. Despite the initial propagation, none of these organoids achieved long‐term proliferation or tolerated cryopreservation, confirming the challenging nature of establishing ACC cell lines. Nevertheless, the biopsy‐derived early passage organoid developed subcutaneous tumors in immunodeficient mice. The xenograft tumor histologically resembled the original tumor and gave rise to infinitely propagating organoids with solid features and high levels of trypsin secretion. Moreover, the organoid stained positive for carboxylic ester hydrolase, a specific ACC marker, but negative for the duct cell marker CD133 and the endocrine lineage marker synaptophysin. Hence, we concluded the derivation of a novel ACC cell line of the pure exocrine lineage, designated HS‐1. Genomic analysis revealed extensive copy number alterations and mutations in EP400 in the original tumor, which were enriched in primary organoids. HS‐1 displayed homozygous deletion of CDKN2A, which might underlie xenograft formation from organoids. Although resistant to standard cytotoxic agents, the cell line was highly sensitive to the proteasome inhibitor bortezomib, as revealed by an in vitro drug screen and in vivo validation. In summary, we document a novel ACC cell line, which could be useful for ACC studies in the future. Abstract : By combining the organoid culture and xenograft formation, a novel cell line HS‐1 was eventually established from a biopsy of acinar cell carcinoma (ACC), a rare subtype of pancreatic cancer, for the first time as an organoid. HS‐1 is positive for carboxylic ester hydrolase (CEH), a highly specific acinar cell marker, and secretes trypsin abundantly, but is negative for the duct cell marker CD133, thereby retaining the features of acinar cells and the original tumor. HS‐1 harbors a missense mutation in EP400 and a 30‐Mb deletion encompassing CDKN2A. Drug screening identified the proteasome inhibitor bortezomib as a potential ACC therapeutic. This cell line will be useful for further ACC studies.